PENGEMBANGAN MEDIA FLASHCARD DALAM PAPAN DART UNTUK MENANAMKAN JIWA NASIONALISME PADA SISWA SEKOLAH DASAR - Anna Roosyanti; Vivi Andalusia Dewi; Desi Eka Pratiwi (PGSD UNIKA SANTU PAULUS RUTENG, 2021)
This development research aims to produce simple media products that are easy to apply in classroom learning, made in the form of flashcards. Flashcard media can be used for both classical and individual learning for elementary school students, to determine (1) the validity and feasibility of the media including pictures, materials and language; (2) practicality and effectiveness in using Flashcard media, especially Civics subjects in the material of Instilling the Spirit of Nationalism for Grade V students of SDN Pacarkeling VI Surabaya. This research was conducted at SDN Pacarkeling VI Surabaya in the even semester of the 2019/2020 school year. The development research method adopted the ADDIE model with several stages, namely the Analysis, Design, Development, Implementation, and Evaluation stages. Guidelines for product feasibility assessment using data analysis techniques from material experts get a score of 96% and fall into the appropriate criteria, from media experts get a score of 90% and fall into the feasible criteria, and in terms of language shows a score of 97.5% which is in the good category. Keywords: Media development, flashcards, Civics.